Peran Kelembagaan Lokal dalam Pengelolaan Situ Tujuh Muara (Ciledug), Kota Tangerang Selatan - Inah, Nasta (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
The existence of Situ are needed within a river basin (DAS) because it serves as a temporary surface water runoff. Various research findings indicate that the number of situ around Jakarta were declining and the extent is shrinking due to various things, one of which is the change of function. One of the Situ in South Tangerang which changed the function so that it resulted in a narrowing of the area occurred in Situ Tujuh Muara or commonly known as Situ Ciledug. Situ Ciledug is a small reservoir designed for a flood control system. In the rainy season, it is capable of storing run-off water. Nevertheless, as a result of unclear governance jurisdiction in the lake management, its original function has been abandoned and to some extend its function has changed. Consequently the area of situ tends to become narrow and reduce its flood control function. This study aims to determine the role of local institution, especially at grass root level, in managing Situ Ciledug. By using in-depth interview and field observation, this study shows that Situ Ciledug which should be protected as preservation area, has been converted into residential and business area, so that it caused the reduction of water body. Local institutions are actively participating in the maintenance of situ and provide positive impact on the expansion of its coverage area.